Effect of alone and tank mix application of herbicides on weed infestation and productivity of kharif Maize (Zea mays L.) - Ghrasiram, Ghrasiram; kumar, Mukesh; Kumar, Vinod; Kumar, Mritunjay; Laik, Ranjan Kumar (Journal of Cereal Research, 2020)
A field trial was conducted during the kharif season at agricultural research farm of Trihut college of Agriculture (TCA) Dholi under the RPCAU Pusa, Samastipur (Bihar) to find out the efficiency of sole and sequential application of herbicides on weeds and productivity of the maize crop. A total of eleven treatments viz: Weedy check, Topramezone @ 25.2 g ha-1, Tembotrione @ 120 g ha-1, Atrazine @ 1 kg ha-1 fb hand weeding at 25 DAS, Atrazine @ 0.75 kg ha-1 fb topramezone @ 25.2 g ha-1, Atrazine 0.75 kg fb tembotrione 120 g ha-1, Atrazine 1.0 kg ha-1fbtopramezone 25.2 g ha-1, Atrazine 1.0 kg ha-1fb tembotrione 120 g ha-1, Topramezone 25.2 g ha-1+ atrazine @ 0.75 kg ha-1, Tembotrione @ 120 g ha-1 + atrazine @ 0.75 kg ha-1, Weed free were tested in randomized block design with three replication. A total of twelve weed species comprised of four grasses, seven broad leaved weeds and one sedge were recorded in experiment field. The application of atrazine @ 1.0 kg ha-1 fb tembotrione @ 0.120 kg ha-1 significantly reduced the weed density of grass weeds, broad leaved weeds and total weeds and its dry weight compared to all other weed control treatments. This treatment had weed control efficiency (WCE) of 78 % and weed index 2.7%. Thereby, recorded higher yield attributes and grain yield (6.24 t ha-1) which was at par with weed free (6.42 tha-1). Therefore, it may be concluded that application of atrazine @ 1.0 kg ha-1 fb tembotrione @ 0.120 kg ha-1 as effective weed control practice for kharif maize